2021
DOI: 10.3390/app11188489
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Learner for Amharic Sentiment Classification

Abstract: The emergence of the World Wide Web facilitates the growth of user-generated texts in less-resourced languages. Sentiment analysis of these texts may serve as a key performance indicator of the quality of services delivered by companies and government institutions. The presence of user-generated texts is an opportunity for assisting managers and policy-makers. These texts are used to improve performance and increase the level of customers’ satisfaction. Because of this potential, sentiment analysis has been wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Deep ensemble learning models combine the advantages of deep learning and ensemble learning to improve the generalization performance of the model. In this regard, several researchers have used ensemble learning in their studies [41][42][43][44].…”
Section: Related Workmentioning
confidence: 99%
“…Deep ensemble learning models combine the advantages of deep learning and ensemble learning to improve the generalization performance of the model. In this regard, several researchers have used ensemble learning in their studies [41][42][43][44].…”
Section: Related Workmentioning
confidence: 99%
“…Using three publicly available datasets, SMOTE has shown performance gains in tweet polarity classification [26]. Similarly, Neshir et al [27] have shown that SMOTE is improving the performance of sentiment classification using four datasets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, many studies have attempted to address the issue of biased data, mainly employing two methods: sample re-sampling and sample reweighting. Sample re-sampling includes over-sampling [9], under-sampling, and data augmentation. Sample reweighting, on the other hand, assigns weights to each sample based on a weighted function, adjusting the impact of each sample on the model through weighted losses.…”
Section: Introductionmentioning
confidence: 99%